Sequential Therapy of Linezolid and Contezolid to Treat Hematogenous Lung Abscess Caused by Staphylococcus aureus in a Congenital Cerebral Hypoplasia Patient: A Case Report - Zhou S; Xin C; Liu W (Infection and Drug Resistance)
Shuang Zhou,1 Chengqi Xin,2– 5 Wenjuan Liu1 1Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People’s Republic of China; 2Stem Cell Clinical Research Center, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People’s Republic of China; 3National Local Joint Engineering Laboratory, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People’s Republic of China; 4National Genetic Test Center, The First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People’s Republic of China; 5Liaoning Key Laboratory of Frontier Technology of Stem Cell and Precision Medicine, Dalian Innovation Institute of Stem Cell and Precision Medicine, Dalian, Liaoning, People’s Republic of ChinaCorrespondence: Wenjuan Liu; Chengqi Xin, Email liuwenjuan880424@126.com; chengqixin@126.comAbstract: Staphylococcus aureus is a common pathogen of hematogenous lung abscesses. The increased resistance of S. aureus to antibiotics makes infections difficult to treat, often resulting in a poor prognosis. Therefore, it is important to identify S. aureus infections as early as possible and evaluate its sensitivity and resistance to antibiotics, to formulate an appropriate treatment plan. Oxazolidinone antibiotics exhibit potent antibacterial activity against multidrug-resistant (MDR) S. aureus; however, the adverse effects of linezolid, particularly thrombocytopenia, limit its application. Contezolid may ameliorate the hematologic toxicity associated with linezolid. Here, we report the case of a patient with congenital cerebral hypoplasia who was hospitalized due to fever and multiple abscesses in both lungs. In the context of negative blood culture results, the final diagnosis of MDR S. aureus as the causative agent of hematogenous lung abscess was confirmed using macrogenomic next-generation sequencing (mNGS) and targeted next-generation sequencing (tNGS). The patient was treated with linezolid but developed significant thrombocytopenia, so switching to sequential therapy with contezolid, the patient’s platelet counts returned to normal and his condition improved significantly.Keywords: hematogenous lung abscess, Staphylococcus aureus, linezolid, contezolid, next-generation sequencing, congenital cerebral hypoplasia